Effect of altitude on second-generation blood tests to detect erythropoietin abuse by athletes - Ashenden, M. J.; Gore, C. J.; Parisotto, R.; Sharpe, K.; Hopkins, W. G.; Hahn, A. G. (Acta Haematologica, 2003)
Background and Objectives: ON- and OFF-model scores derived from blood parameters sensitive to erythropoiesis have been shown to be a useful tool to identify athletes who are currently injecting erythropoietin to enhance performance or those who have recently stopped doing so. We investigated changes in blood parameters and model scores during and after exposure to terrestrial and simulated altitudes. Design and Methods: We retrospectively evaluated changes in hematologic data collected from 19 elite cyclists who lived and trained 2690 m above sea level for 26-31 days, from six elite Kenyan runners who lived 2100 m above sea level but descended to compete at sea level competitions, and from 39 well-trained subjects who resided at sea level but slept at a simulated altitude of 2650-3000 m for 20-23 days of either consecutive or intermittent nightly exposure. Results: Upon ascent to a terrestrial altitude, ON- and OFF-model scores increased immediately, mainly because of an increase in hemoglobin concentration. Scores had not returned fully to baseline three weeks after return to sea level, because of the persistence of the raised hemoglobin concentration for the ON and OFF scores and a fall in reticulocyte percentage for OFF scores. Effects were smaller or negligible for simulated altitude. For Kenyan runners, ON- and OFF-model scores decreased within seven days of descent to sea level. Interpretation and Conclusions: Our results reinforce the notion that caution should be exercised when interpreting blood results from athletes who have recently been exposed to either terrestrial or simulated altitude, and appropriate allowance should be made for the effect of altitude on blood model scores.